Mapping Digital Marketing Strategy Study with Using Bibliometric Analysis - Kiki Dianti; N Nurkomalasari; Fazri Wima Maulana; Kartika Puspitasari Arrochimmi; Adi Setiawan (Apollo: Journal of Tourism and Business, 2024)
Technology has a big and significant impact on everyone's life. This is due to the increasing development of technology from time to time and is supported by the internet. Until now, the internet has become a necessity for society, because the internet supports all community activities in terms of communication and information, and makes it easier for everyone, whether working, studying or carrying out other activities. In this case, ever-increasing progress means that everyone can take advantage of a situation that can be called digital technology. This allows advertising targeting to the general public which is very focused on communicating with each other, tracking potential buyers and engaging them in related content. Advances in communication and network technology, especially the internet, provide the infrastructure needed for businesses that are run using the internet. The very rapid development of computer and telecommunications technology (information technology) today has resulted in a revolution in the world of trade and industry. In this research, the author used a qualitative research method with a bibliometric approach. In this bibliometric approach there are four analyses, namely, co-authoring analysis, bibliometric network visualization analysis, overlay visualization analysis, and density visualization analysis. This provides an overview and a mapping to the reader regarding a preparation related to Digital Marketing Strategy